The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12889-020-09873-1
|View full text |Cite
|
Sign up to set email alerts
|

Management of uncomplicated malaria among children under five years at public and private sector facilities in Mali

Abstract: Background Prompt and effective malaria diagnosis and treatment is a cornerstone of malaria control. Case management guidelines recommend confirmatory testing of suspected malaria cases, then prescription of specific drugs for uncomplicated malaria and for severe malaria. This study aims to describe case management practices for children aged 1–59 months seeking treatment with current or recent fever from public and private, rural and urban health providers in Mali. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Recent studies from Angola [ 18 , 33 ], Guinea [ 34 ], Kenya [ 19 , 35 , 36 ], Malawi [ 37 ], and Zambia [ 38 40 ] point to improved HCW adherence to test and treat policy. However, in other countries, like Mozambique [ 31 , 41 ], Madagascar [ 42 ], Congo [ 43 ], Cameroon [ 44 ], and Mali [ 45 ] gains have been less impressive.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies from Angola [ 18 , 33 ], Guinea [ 34 ], Kenya [ 19 , 35 , 36 ], Malawi [ 37 ], and Zambia [ 38 40 ] point to improved HCW adherence to test and treat policy. However, in other countries, like Mozambique [ 31 , 41 ], Madagascar [ 42 ], Congo [ 43 ], Cameroon [ 44 ], and Mali [ 45 ] gains have been less impressive.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years (2013–2018), children with a caregiver having some secondary education were even significantly less likely to receive blood tests and recommended medications for malaria [ 20 ]. In another study in Mali, caregiver education was not found to be associated with incorrect case management of uncomplicated malaria among children under five years at public and private sector facilities [ 28 ]. The discrepancies in the associations between SES and quality of malaria case management might be explained by differences in research methods (e.g., different study populations, different sampling methods).…”
Section: Discussionmentioning
confidence: 99%
“…The overall Plasmodium falciparum incidence rate was estimated at 84/1,000 person-months, and its prevalence was estimated at over 40% in the two first surveys and 68.9% in the third survey" [23]. This study was restricted to two seasons which doesn't give an over view of an adequate result in the course of the year.…”
Section: Prevalence Of Malaria Among Toddlersmentioning
confidence: 99%